DOMESTIC VIOLENCE AND ITS REFLECTIONS IN THE SCHOOL ENVIRONMENT - Borges, Ismailde; Ribeiro, Marcio (Revista Gênero e Interdisciplinaridade, 2024)
This study focused on the correlated expressions of school violence against the new social configurations and their implications in the educational scenario. The objective of this study was to analyze the literature already produced about this topic, about school violence in the current scenario. The method adopted in this study was the integrative review of literature, with the searches occurring from January to March, 2019, in the databases Lilacs, Medline, Scielo. The results pointed out that violence in the school scene is one of the realities that most frighten the school community and society in general, resulting in moral, psychological, social and physical damages. It was verified that there are several configurations of violence within the school, among them it stands out; the psychological, verbal, symbolic and physical, reaching not only students and teachers but all those involved in the educational process. It was verified that the family influences the development of school violence, since children witness situations of violence in their homes, seek to reproduce these acts both in school and outside, causing harm and serious consequences for all involved. It was verified that security technology is of paramount importance in the combat, control and identification of school violence, in order to have the effective and appropriate mechanisms to intervene in this reality. It is concluded that there is a need to carry out more research on this subject, since school violence is an emerging phenomenon and has made several victims in the last decades, therefore, there is a need for effective interventions, and of public security professionals.